Influence of Teachers’ Subject Competence and Teaching Experience on Use of Instructional Strategies to Enhance Pupils Literacy Skills in Busia County, Kenya - Otwate Paul; Nyakwara Begi; Margaret Mwangi (Randwick International of Education and Linguistics Science Journal, 2021)
Language skills in young children provides a foundation to a better acquisition of cognitive, social, physical and emotional skills useful in the later years of life for children. It also enhances smooth transition, performance, and retention and completion rate in school for children. The paper presents findings from a study conducted to establish the influence of teacher’s subject competence and teaching experience on use of instructional strategies to enhance development of literacy skills in children in lower grade in Nambale Sub-county, Busia County Kenya. It is paramount to generate evidence based understanding of the primary role of teachers for language in enhancing children’s literacy skills to improve their chances of acquiring quality and inclusive education later in life. Researchers aimed to establish the influence of teacher’s subject competence and teaching experience during foundation level at which children should primarily acquire basic literacy skills to facilitate a smooth transition to later grades.